Frecuencia de la parasitosis intestinal y del estado nutricional en niños menores de 5 años atendidos en el Centro de Salud San Jerónimo. Andahuaylas, 2016. - Cárdenas Castillo, Karina (2019)
The intestinal parasitism constitutes a problem of major incident in the infantile population of low socioeconomic level of Peru, due that these parasites could enter to the organisms by different tracks, by the different precarious conditions and inadequate habits of hygiene and care, facilitating its transmission and conservation. The present investigation was studied with the purpose to determine the Frequency of the intestinal parasitism and of the Nutritional State in Children minor 5 Years Old Attended in the Center of Health San Jerónimo, Andahuaylas. 266 stool samples were taken from the children, also in this the nutritional status was determined according to weight, height and age of the children; the values obtained were analyzed by the Chi - square test with a confidence level of 96% and the evaluation of the nutritional state was calculated with the index of body mass, classifying malnourished, normal, overweight and obese according to the percentile obtained. It was a study where it was used as an inductive method, analysis and synthesis; of descriptive, explanatory and correlational level; of basic - descriptive type; with experimental design - transversal. The methodology began with the compilation of stool samples in wide-mouthed plastic bottles duly labeled, being analyzed by the technique of spontaneous sedimentation of Tello; later observed to the microscope to 10x and 40x. The results show a high frequency of parasitism, mostly by protozoa; however, this could be a factor, but not the only one, responsible determinant of nutritional status. About of the half of the population has a normal nutritional state, despite the fact that a relatively high percentage presents undernourished nutritional status (16.8%), nutritional status of overweight (19.2%), most often were the protozoan type parasites (39%).